Unknown syndrome: ischiadic hypoplasia, renal dysfunction, immunodeficiency, and a pattern of minor congenital anomalies. - Braegger, C (1991)
We report a 6 year old male with a pattern of malformations and anomalies including intrauterine growth retardation, microcephaly, psychomotor retardation, a pattern of craniofacial anomalies (flat face, hypertelorism, epicanthic folds, strabismus, short nose, low set ears), hypospadias and cryptorchidism, bilateral partial cutaneous syndactyly between fingers 2 to 5 and toes 2 to 4, postaxial polydactyly of the fingers and toes, severe conductive hearing loss, hypoplasia of the ischiadic bones, complex renal dysfunction, hypogammaglobulinaemia with proneness to bacterial infections of the upper and lower respiratory tract, and recurrent pseudomembranous enterocolitis. The parents are cousins of Turkish origin.